The current temperature: A survey of post-resuscitation care across Australian and New Zealand intensive care units - Bray, Janet; Cartledge, Susie; Finn, Judith; Eastwood, Glenn; McKenzie, Nicole; Stub, Dion; Straney, Lahn; Bernard, Stephen (2020)
Aim: Targeted temperature management (TTM) in post-resuscitation care has changed dramatically over the last two decades. However, uptake across Australian and New Zealand (NZ) intensive care units (ICUs) is unclear. We aimed to describe post-resuscitation care in our region, with a focus on TTM, and to gain insights into clinician’s opinions about the level of evidence supporting TTM.